Modeling Disease Progression: Angiotensin II Indirectly Inhibits Nitric Oxide Production via ADMA Accumulation in Spontaneously Hypertensive Rats - Wang, Haidong; Jiang, Hao; Liu, Haochen; Zhang, Xue; Ran, Guimei; He, Hua; Liu, Xiaoquan (Frontiers in Physiology, 2016)
Nitric oxide (NO) production impairment is involved in the onset and development of hypertension. Although NO production impairment in spontaneously hypertensive rat (SHR) has been reported in a variety of researches, the time course of this progressive procedure, as well as its relationship with asymmetric dimethylarginine (ADMA) and angiotensin II (Ang II), has not been quantified. The aim of this research is to establish a mechanism-based disease progression model to assess Ang II and ADMA’s inhibition of NO production in SHR’s disease progression with/without ramipril’s intervention. SHR were randomly divided into three groups: one disease group (n=8) and two treatment groups (n=8 for each group) ：standard treatment group (receiving ramipril 2mg/kg*day) and intensive treatment group (receiving ramipril 10mg/kg*day). ADMA, Ang II, NO and SBP were determined weekly. Intensive treatment with ramipril was found to have no further attenuation of plasma NO and ADMA than standard treatment beyond its significantly stronger antihypertensive effects. Four linked turnover models were developed to characterize the profiles of ADMA, Ang II, NO and SBP during hypertensive disease progression with/without ramipril intervention. Our model described Ang II and ADMA’s contribution to NO production impairment and their responses to ramipril treatment throughout the disease progression in SHR. Model simulations suggested that Ang II affected NO production mainly through inhibiting ADMA elimination rather than affecting nitric oxide synthase (NOS) directly.